1990
DOI: 10.3109/10799899009064669
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Recognizing the Benzodiazepine Receptor of Chick Embryo Brain

Abstract: The benzodiazepine receptor (BZDR) of the embryonic chick brain contained three subunit proteins with molecular weights of 48-kilodalton (KD), 50-KD and 51-KD at a pI of 5.6, as demonstrated by two-dimensional gel electrophoresis and fluorography of the 3H-flunitrazepam (FNZ)-photolabeled receptor. Monoclonal antibodies (mAB) against the receptor were produced by using the spleen cells of one mouse immunized with the three subunit proteins extracted from SDS-PAGE gels. When the radioligand-labeled membranes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Dietl et al (1988) also only found modest ligand binding for BDZ sites in the visceral basal ganglia in pigeon. In chicks, the abundance of GABAA/ BDZ receptors in the visceral basal ganglia has also been found to be modest with ligand binding, immunohistochemistry, and in situ hybridization histochemistry (Stewart et al, 1988;Yin and Fan, 1990;Bateson et al, 1991;Glencorse et al, 1991). Our immunohistochemical data, however, showed that the visceral basal ganglia indeed contained a mat of dendrites labeled for GABAA~BDZ receptors, resembling our previously observed GABAergic terminals (which surround dendrites).…”
Section: CL Veenman Et Alsupporting
confidence: 85%
See 1 more Smart Citation
“…Dietl et al (1988) also only found modest ligand binding for BDZ sites in the visceral basal ganglia in pigeon. In chicks, the abundance of GABAA/ BDZ receptors in the visceral basal ganglia has also been found to be modest with ligand binding, immunohistochemistry, and in situ hybridization histochemistry (Stewart et al, 1988;Yin and Fan, 1990;Bateson et al, 1991;Glencorse et al, 1991). Our immunohistochemical data, however, showed that the visceral basal ganglia indeed contained a mat of dendrites labeled for GABAA~BDZ receptors, resembling our previously observed GABAergic terminals (which surround dendrites).…”
Section: CL Veenman Et Alsupporting
confidence: 85%
“…The septum is lightly (GABAAIBDZ) to moderately (GABAB) labeled for the receptors, but dense in GABAergic terminals. Other authors have also shown a relatively low abundance of GABA receptor labeling in the avian septum (Dietl et al, 1988;Stewart et al, 1988;Yin and Fan, 1990;Bateson et al, 1991;Canonaco et al, 1991Canonaco et al, , 1992Glencorse et al, 1991).…”
Section: Gabaergic Terminals Gaba Receptorsmentioning
confidence: 93%
“…The percentage of cells containing ␣ 1 mRNA is lower than that immunostained by mAb 2C3. The difference probably results from that mAb 2C3 recognizes two putative ␣-subunits [Yin and Fan, 1990].…”
Section: Gaba a R ␣ 1 -Subunit Mrnamentioning
confidence: 93%
“…Fluorography was carried out according to previous procedures [Yin and Fan, 1990]. In brief, cultured cell homogenates were incubated with 5 nM 3 H-FNZ in PBSS for 60 min on ice followed by irradiation with long-wavelength ultraviolet light at a distance of 3 cm for 45 min at 4°C.…”
Section: Photolabeling Sodium Dodecyl Sulfate Polyacrylomide Gel Elementioning
confidence: 99%
See 1 more Smart Citation